Pleistocene megafauna coprolite analysis: inferences about dietary habits and vegetation in a highland ecosystem of South America - Nadia J. Velázquez; M. Eugenia Mosca Torres; Romina S. Petrigh; M. Laura Benvenuto; M. Fernanda Rodríguez; Federico M. Bobillo; Lidia S. Burry; Jorge G. Martínez; Carlos A. Aschero (Quaternary Science Reviews, 2026)

Changes in barley malting quality and mycotoxin contamination associated with warm nights and Fusarium graminearum infection under climate change scenarios - Mauro Martínez; Carolina Manno; Agustín F. Arata; María I. Dinolfo; Eduardo De Gerónimo; Juan Ignacio Poo; Agustín Mosca; Germán González; Sebastián A. Stenglein (European Journal of Plant Pathology, 2026)

Pesticide removal by fluvial biofilms in lowland streams under different land uses and agricultural seasons - M. A. Mujica; E. De Gerónimo; A. Mosca; S. L. Fanelli; A. H. Paracampo; J. Cochero (International Journal of Environmental Science and Technology, 2026)

Genome resources of Pseudomonas sp. CFBP 5748 and Pseudomonas sp. CFBP 5750, fluorescent pseudomonads associated with tomato pith necrosis (FPTPN), clarify their position within the P. corrugata phylogenetic subgroup - G. Dimaria; D. Nicotra; A. Mosca; M. Fischer-Le Saux; P. Portier; V. Catara (Journal of Plant Pathology, 2026)

Efficacy and innocuity of lotilaner in the treatment of otodectic mange in ferrets - M. Legain; A. Idee; D. Mardini; M. Rene-Martellet; M. Mosca; D. Pin (Veterinary Parasitology, 2024)

Mosquito management strategies in European rice fields: Environmental and public health perspectives - Mikel A. González; Alexandra Chaskopoulou; Loukas Georgiou; Eva Frontera; Francisco Cáceres; Montse Masia; Raquel Gutiérrez-Climente; Gregory L’ Ambert; Hugo Osório; Gonçalo Seixas; Francesco Defilippo; Mattia Calzolari; et al. (Journal of Environmental Management, 2024)

Second-tier trio exome sequencing after negative solo clinical exome sequencing: an efficient strategy to increase diagnostic yield and decipher molecular bases in undiagnosed developmental disorders - Frederic Tran Mau-Them; Sebastien Moutton; Caroline Racine; Antonio Vitobello; Ange-Line Bruel; Sophie Nambot; Steven A. Kushner; Femke M. S. de Vrij; Daphné Lehalle; Nolwenn Jean-Marçais; François Lecoquierre; Julian Delanne; et al. (Human Genetics, 2020)

Environmental effects on fine‐scale spatial genetic structure in four Alpine keystone forest tree species - Elena Mosca; Erica A. Di Pierro; Katharina B. Budde; David B. Neale; Santiago C. González‐Martínez (Molecular Ecology, 2018)
Genetic responses to environmental changes take place at different spatial scales. While the effect of environment on the distribution of species' genetic diversity at large geographical scales has been the focus of several recent studies, its potential effects on genetic structure at local scales are understudied. Environmental effects on fine‐scale spatial genetic structure ( FSGS ) were investigated in four Alpine conifer species (five to eight populations per species) from the eastern Italian Alps. Significant FSGS was found for 11 of 25 populations. Interestingly, we found no significant differences in FSGS across species but great variation among populations within species, highlighting the importance of local environmental factors. Interannual variability in spring temperature had a small but significant effect on FSGS of Larix decidua , probably related to species‐specific life history traits. For Abies alba , Picea abies and Pinus cembra , linear models identified spring precipitation as a potentially relevant climate factor associated with differences in FSGS across populations; however, models had low explanatory power and were strongly influenced by a P. cembra outlier population from a very dry site. Overall, the direction of the identified effects is according to expectations, with drier and more variable environments increasing FSGS . Underlying mechanisms may include climate‐related changes in the variance of reproductive success and/or environmental selection of specific families. This study provides new insights on potential changes in local genetic structure of four Alpine conifers in the face of environmental changes, suggesting that new climates, through altering FSGS , may also have relevant impacts on plant microevolution.

Habitat selection and coexistence in small mammals of the southern Andean foothills (Argentina) - Agustina Novillo; M. Fernanda Cuevas; Agustina A Ojeda; Ramiro J. A Ovejero; Mosca Torres; M. Eugenia; Ricardo A Ojeda (Mammal Research, 2017)

Climate-related adaptive genetic variation and population structure in natural stands of Norway spruce in the South-Eastern Alps - Erica A. Di Pierro; Elena Mosca; Duccio Rocchini; Giorgio Binelli; David B. Neale; Nicola La Porta (Tree Genetics & Genomes, 2016)

Post-aerobic digestion of waste sludge: performance analysis and modelling of nitrogen fate under alternating aeration - M. C. Tomei; N. A. Carozza; D. Mosca Angelucci (International Journal of Environmental Science and Technology, 2016)

The geographical and environmental determinants of genetic diversity for four alpine conifers of the E uropean A lps - E. Mosca; A. J. Eckert; E. A. Di Pierro; D. Rocchini; Nicola La Porta; P. Belletti; D. B. Neale (Molecular Ecology, 2012)
Climate is one of the most important drivers of local adaptation in forest tree species. Standing levels of genetic diversity and structure within and among natural populations of forest trees are determined by the interplay between climatic heterogeneity and the balance between selection and gene flow. To investigate this interplay, single nucleotide polymorphisms ( SNP s) were genotyped in 24 to 37 populations from four subalpine conifers, Abies alba Mill., Larix decidua Mill., Pinus cembra L. and Pinus mugo Turra, across their natural ranges in the Italian Alps and Apennines. Patterns of population structure were apparent using a Bayesian clustering program, STRUCTURE , which identified three to five genetic groups per species. Geographical correlates with these patterns, however, were only apparent for P. cembra . Multivariate environmental variables [i.e. principal components (PCs)] were subsequently tested for association with SNP s using a Bayesian generalized linear mixed model. The majority of the SNP s, ranging from six in L. decidu a to 18 in P. mugo , were associated with PC 1, corresponding to winter precipitation and seasonal minimum temperature. In A. alba , four SNP s were associated with PC 2, corresponding to the seasonal minimum temperature. Functional annotation of those genes with the orthologs in Arabidopsis revealed several genes involved in abiotic stress response. This study provides a detailed assessment of population structure and its association with environment and geography in four coniferous species in the Italian mountains.

Lack of feral livestock interference with native guanaco during the dry season in a South American desert - Ramiro J. A. Ovejero; Pablo Acebes; Juan E. Malo; Juan Traba; Maria Eugenia Mosca Torres; Carlos E. Borghi (European Journal of Wildlife Research, 2011)

Nasal cytology: the “infectious spot”, an expression of a morphological-chromatic biofilm - M. Gelardi; G. Passalacqua; M. L. Fiorella; A. Mosca; N. Quaranta (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Studying root distribution with geostatistics - T. Vamerali; M. Guarise; A. Ganis; F. Zanetti; G. Mosca (Plant Biosystems, 2008)

Fibrous root turnover and growth in sugar beet (Beta vulgaris var. saccharifera) as affected by nitrogen shortage - T. Vamerali; A. Ganis; S. Bona; G. Mosca (Plant and Soil, 2003)

Analysis of root images from auger sampling with a fast procedure: a case of application to sugar beet - T. Vamerali; M. Guarise; A. Ganis; S. Bona; G. Mosca (Plant and Soil, 2003)

A comparison of root characteristics in relation to nutrient and water stress in two maize hybrids - T. Vamerali; M. Saccomani; S. Bona; G. Mosca; M. Guarise; A. Ganis (Plant and Soil, 2003)

Inhibition of mycophenolic acid glucuronidation by niflumic acid in human liver microsomes - M. Vietri; A. Pietrabissa; F. Mosca; G. Pacifici (European Journal of Clinical Pharmacology, 2002)

Mycophenolic acid glucuronidation and its inhibition by non-steroidal anti-inflammatory drugs in human liver and kidney - M. Vietri; A. Pietrabissa; F. Mosca; G.M. Pacifici (European Journal of Clinical Pharmacology, 2000)

Differential inhibition of hepatic and duodenal sulfation of (−)-salbutamol and minoxidil by mefenamic acid - M. Vietri; A. Pietrabissa; R. Spisni; F. Mosca; G. M. Pacifici (European Journal of Clinical Pharmacology, 2000)

Inhibition of human liver phenol sulfotransferase by nonsteroidal anti-inflammatory drugs - M. Vietri; C. De Santi; A. Pietrabissa; F. Mosca; G. M. Pacifici (European Journal of Clinical Pharmacology, 2000)

An approach to minirhizotron root image analysis - T. Vamerali; A. Ganis; S. Bona; G. Mosca (Plant and Soil, 1999)

Catechol- O -methyltransferase: variation in enzyme activity and inhibition by entacapone and tolcapone - C. De Santi; P. C. Giulianotti; A. Pietrabissa; F. Mosca; G. M. Pacifici (European Journal of Clinical Pharmacology, 1998)